2019
DOI: 10.1016/j.hrthm.2019.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Permanent left bundle branch area pacing for atrioventricular block: Feasibility, safety, and acute effect

Abstract: BACKGROUND Left bundle branch area pacing (LBBAP), a new pacing approach, lacks adequate evaluation. OBJECTIVE To assess the feasibility, safety, and acute effect of permanent LBBAP in patients with atrioventricular block (AVB). METHODS A total of 33 AVB patients with indications for ventricular pacing were recruited. Electrocardiograms, pacing parameters, echocardiographic measurements, and complications associated with LBBAP were evaluated perioperatively and at 3-month follow-up. Successful LBBAP was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
219
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(243 citation statements)
references
References 23 publications
16
219
4
4
Order By: Relevance
“…Continuous data were presented as mean ± standard deviation. We used the Student's t‐test to compare continuous variables and the χ 2 test to compare categorical variables. Proportions were compared with use of the Fisher exact test.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous data were presented as mean ± standard deviation. We used the Student's t‐test to compare continuous variables and the χ 2 test to compare categorical variables. Proportions were compared with use of the Fisher exact test.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the left bundle branch pacing (LBBP) has emerged as an alternative method for physiological pacing . LBBP is characterized with a low and stable pacing capture threshold, relatively narrow QRS duration (QRSd) due to fast left ventricular activation, and direct excitation of the diseased left bundle branch (LBB) . Our previous study demonstrated the procedural and clinical feasibility of LBBP via a transventricular‐septal approach .…”
Section: Introductionmentioning
confidence: 99%
“…The main findings were: Almost all patients (115/117, 98.3%) had visible LBB potentials, which is much more frequent than the rates of 30 to 70% previously reported in the literature 3–6 . These findings are due, first, to the highly experienced operators.…”
Section: Comparison Of Advantages and Disadvantages Of His Bundle Pacmentioning
confidence: 77%